Jumping exercise preserves bone mineral density and mechanical properties in osteopenic ovariectomized rats even following established osteopenia - Okubo, R.; Sanada, L. S.; Castania, V. A.; Louzada, M. J. Q. [UNESP]; Paula, F. J. A. de; Maffulli, N.; Shimano, A. C. (Springer, 2017)
The effects of jump training on bone structure before and after ovariectomy-induced osteopenia in rats were investigated. Jumping exercise induced favorable changes in bone mineral density, bone mechanical properties, and bone formation/resorption markers. This exercise is effective to prevent bone loss after ovariectomy even when osteopenia is already established. The present study investigated the effects of jump training on bone structure before and after ovariectomy-induced osteopenia in 80 10-week-old Wistar rats. Forty rats (prevention program) were randomly allocated to one of four equal groups (n = 10): sham-operated sedentary (SHAM-SEDp), ovariectomized (OVX) sedentary (OVX-SEDp), sham-operated exercised (SHAM-EXp), and OVX exercised (OVX-EXp). SHAM-EXp and OVX-EXp animals began training 3 days after surgery. Another 40 rats (treatment program) were randomly allocated into another four groups (n = 10): sham-operated sedentary (SHAM-SEDt), OVX sedentary (OVX-SEDt), sham-operated exercised (SHAM-EXt), and OVX exercised (OVX-EXt). SHAM-EXt and OVX-EXt animals began training 60 days after surgery. The rats in the exercised groups jumped 20 times/day, 5 days/week, to a height of 40 cm for 12 weeks. At the end of the experimental period, serum osteocalcin, follicle-stimulating hormone (FSH) dosage, dual X-ray absorptiometry (DXA), histomorphometry, and biomechanical tests were analyzed. The OVX groups showed higher values of FSH and body weight (p < 0.05). DXA showed that jump training significantly increased bone mineral density of the femur and fifth lumbar vertebra (p < 0.05). The stiffness of the left femur and fifth lumbar vertebra in the exercised groups was greater than that of the sedentary groups (p < 0.05). Ovariectomy induced significant difference in bone volume (BV/TV, percent), trabecular separation (Tb.Sp, micrometer), and trabecular number (Tb.N, per millimeter) (p < 0.05) compared to sham operation. Jump training in the OVX group induced significant differences in BV/TV, Tb.Sp, and Tb.N and decreased osteoblast number per bone perimeter (p < 0.05) compared with OVX nontraining, in the prevention groups. Osteocalcin dosage showed higher values in the exercised groups (p < 0.05). Jumping exercise induced favorable changes in bone mineral density, bone mechanical properties, and bone formation/resorption markers. Jump training is effective to prevent bone loss after ovariectomy even when osteopenia is already established.
Keywords: Exercise therapy; Osteopenia; Ovariectomy; Rehabilitation medicine